Cover Feature: N3‐Kethoxal‐Based Bioorthogonal Intracellular RNA Labeling (ChemBioChem 9/2021). (5th May 2021) - Huang, Jinguo; Zhao, Ruiqi; Mo, Jing; Wang, Fang; Weng, Xiaocheng; Zhou, Xiang
Abstract : The make‐up of RNA : This cover feature describes a new strategy to modify RNA combined with N3 ‐kethoxal labeling and an intracellular biorthogonal reaction. N3 ‐kethoxal with the advantages of small size, low toxicity, excellent membrane‐permeable, and high reactivity, serves to bring an azido group to the RNA molecules. Next the cell‐permeable dibenzocyclooctyne (DBCO) reagent reacts with azido group to link covalently to the RNA strand, which can be extended to "make‐up" RNA inside the cell for imaging or other functionalization. More information can be found in the Communication by X. Weng, X. Zhou, et al.